2015
DOI: 10.1371/journal.pone.0119138
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Parental Separation and Body Weight, Including Development of Overweight and Obesity Later in Childhood

Abstract: BackgroundEarly parental separation may be a stress factor causing a long-term alteration in the hypothalamic-pituitary-adrenal-axis activity possibly impacting on the susceptibility to develop overweight and obesity in offspring. We aimed to examine the body mass index (BMI) and the risk of overweight and obesity in children whose parents lived separately before the child was born.MethodsA follow-up study was conducted using data from the Aarhus Birth Cohort in Denmark and included 2876 children with measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Two studies found that smaller household size was a risk factor, whereas another study found the opposite. One study found that parents who lived separately before the birth of child (versus together) were more likely to have a child identified as obese.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that smaller household size was a risk factor, whereas another study found the opposite. One study found that parents who lived separately before the birth of child (versus together) were more likely to have a child identified as obese.…”
Section: Resultsmentioning
confidence: 99%
“…1. Full text review yielded 24 publications for inclusion into the systematic review and meta-analyses [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. The list of excluded studies with reasons for exclusion is available in SI 5.…”
Section: Eligible Studies and Characteristicsmentioning
confidence: 99%
“…In our published work on prenatal stress and AGD, relationships were stronger in relation to couple's combined stress (83). We discuss possible explanations in that article 3. Models are stratified by infant sex and adjust for study center, creatinine, age at examination, and weight-for-age Z-score.…”
mentioning
confidence: 93%
“…According to this model, in utero exposures can play a significant role in shaping future physiology and there is particular interest in how prenatal stress 1 may influence fetal development, leading to altered childhood outcomes. Thousands of studies in humans and animal models have examined these issues, focusing on outcomes ranging from immune function (1,2) to metabolism (3,4). The influence of maternal stress can be seen even during fetal development (5,6) and can be long-lasting, persisting into adulthood (7,8).…”
mentioning
confidence: 99%